Prognostic values of tumor necrosis factor-alpha, monocyte chemoattractant protein-1, and neuron-specific enolase in patients with sepsis-associated encephalopathy - Zhu Bingnan; Liu Fengqi; Jia Zhongnan; Chen Zhidong; Wang Luyin (Vojnosanitetski Pregled)
Background/Aim. Sepsis-associated encephalopathy (SAE) is a severe complication of sepsis, characterized by brain dysfunction and associated with a poor prognosis. SAE has a complex pathogenesis, and its severity is in close association with the levels of various serum factors. The aim of the study was to investigate the correlation of tumor necrosis factor (TNF)-α, monocyte chemoattractant protein (MCP)-1, and neuron-specific enolase (NSE) levels with the severity of SAE and to analyze the prognostic values of the three parameters. Methods. This prospective study enrolled 126 patients treated for SAE from June 2020 to June 2022. The levels of TNF-α, MCP-1, and NSE were measured, and the severity of SAE was evaluated using the Sequential Organ Failure Assessment (SOFA) score. Based on the SOFA score, the patients were assigned to two groups: a group with a bad prognosis and a group with a good prognosis. The correlations of TNF-α, MCP-1, and NSE levels with the severity of SAE were analyzed, and their prognostic values were evaluated during a 28-day follow-up. Results. The mean levels of TNF-α, MCP-1, and NSE and the SOFA score of the 126 patients with SAE were 6.52 ± 1.48 pg/mL, 62.53 ± 18.49 pg/mL, 8.61 ± 2.17 ng/mL, and 10.24 ± 2.86 points, respectively. Pearson’s analysis demonstrated significant correlations be-tween TNF-α, MCP-1, and NSE levels and the SOFA score of patients with SAE (r > 0, p < 0.05). Of the 126 patients, 61 (48.4%) had a poor prognosis, while 65 (51.6%) had a good prognosis. Increased serum TNF-α, MCP-1, and NSE levels were risk factors for the poor prognosis of patients with SAE [odds ratio (OR) > 1, p < 0.05]. The areas under the receiver operating characteristic (ROC) curves of serum TNF-α, MCP-1, and NSE levels were all > 0.7, suggesting high predictive values of these parameters. Conclusion. Serum TNF-α, MCP-1, and NSE levels are closely correlated with the severity of SAE and may work as valuable predictors of treatment outcome.